2017
DOI: 10.1002/ijgo.12319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Valsalva maneuver and intraoperative traction measurements in pelvic organ prolapse assessment

Abstract: Measurements of six POP-Q points obtained with traction showed a higher grade of POP than those assessed with Valsalva maneuver. On this basis, surgeons might decide on the extent of surgical procedure after examination under anesthesia; however, preoperative patient counselling would be essential to obtain consent for this approach. The clinical significance of the findings requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Among the three measurements of POP‐Q length, there was a significant change in Gh measurements and no changes in measurements of Tvl and Pb between the two examination methods, which is in agreement with other studies 5 5 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the three measurements of POP‐Q length, there was a significant change in Gh measurements and no changes in measurements of Tvl and Pb between the two examination methods, which is in agreement with other studies 5 5 …”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the development of POP may be due to the neuromuscular blockade and denervation of pelvic floor muscles. The relaxation of levator ani muscles under anesthesia might contribute to an increased degree of descent measured in the operating theatre 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a secondary analysis of data from a prospective case series, which was registered with the local audit department (audit registration 1511). The primary analysis compared the assessment of POP using the POP‐Q system with Valsalva maneuver and intraoperative measurements with mechanical traction . No ethics committee approval or informed consent was required for this study, since it represented an audit of our standard practice.…”
Section: Methodsmentioning
confidence: 99%
“…The primary analysis compared the assessment of POP using the POP-Q system with Valsalva maneuver and intraoperative measurements with mechanical traction. 8 P<0.05 was considered statistically significant. Table 1 shows demographic characteristics of included women and the surgical procedures performed.…”
Section: Methodsmentioning
confidence: 99%